Does child spacing affect children's outcomes? Evidence from a Swedish reform - Per Pettersson-Lidbom; Peter Skogman Thoursie (Institute for Labour Market Policy Evaluation (IFAU), 2009)
In this paper, we provide evidence of whether child spacing affects the future success of children. As an exogenous source of variation in child spacing, we make use of the introduction of an administrative rule in the parental leave benefit system in Sweden. This rule made it possible for a woman to retain her previous high level of parental leave benefits, i.e., 90 percent wage replacement, without entering the labor market between births provided that the interval between the births did not exceed 24 months. The rule had a much larger effect on the birth spacing behavior for native-born mothers compared to foreign-born mothers due to their differential attachment to the labor market. We find that the rule caused a reduction in spacing among native-born mothers as compared to the foreign-born mothers. For individuals born by native-born mothers, the reform also caused a decrease in educational attainment. Thus, this suggests that the effect of spacing children closer has a negative impact on children's future outcomes. We provide additional evidence that this is likely due to the strong effects of early environment on the capacity for human skill development as discussed by Knutsen et al. (2006).
Keywords: J13; J18; 330; Child spacing; parental leave; child school performance; Elternzeit; Familienplanung; Bildungsniveau; Kinder; Frauenerwerbstätigkeit; Schweden